Antioxidant Activity of Taxillus chinensis Parasitizing on Toona sinensis (A. Juss) Roem - Liao, Yanfang; Huo, Lini; Chen, Rui; Li, Peiyuan; Lu, Rumei (Asian Journal of Chemistry, 2013)
The present study describes the in vitro antioxidant activity of petroleum ether, ethyl acetate and n-butanol extracts of Taxillus chinensis living parasitically on Toona sinensis (A. Juss) Roem. The antioxidant activity of the extracts was assessed by using the following methods: 1,1-diphenyl-2-picrylhydrazyl and 2,2'-azo-bis(3-ethylbenzothiazoline-6-sulfonic acid) diamonium salt both free radical scavenging assays and reducing assays. The antioxidant activities of various extracts of T. chinensis from T. sinensis seemed to follow the same trend i.e., n-butanol extracts > ethyl acetate extracts > petroleum ether extracts. The results showed that these extracts, especially the n-butanol extracts, could be considered as natural antioxidants and may be useful for curing diseases arising from oxidative deterioration.